Disaster victim identification operations with fragmented, burnt, or commingled remains: experience-based recommendations - Hans H. de Boer; Julie Roberts; Tania Delabarde; Amy Z. Mundorff; Soren Blau (Oxford University Press, 2020)
Human-made and natural disasters can result in severely fragmented, compromised, and commingled human remains. The related disaster victim identification (DVI) operations are invariably challenging, with the state of the remains potentially precluding some identifications. Practitioners involved in these DVI operations will routinely face logistical, practical, and ethical challenges. This review provides information and guidance derived from first-hand experiences to individuals tasked with managing DVI operations with fragmented human remains. We outline several key issues that should be addressed during disaster preparedness planning and at the outset of an operation, when incident-specific strategies are developed. Specific challenges during recovery and examination of fragmented remains are addressed, highlighting the importance of experienced specialists at the scene and in the mortuary. DNA sample selection and sampling techniques are reviewed, as well as downstream effects of commingling and contamination, which can complicate reconciliation and emphasise the need for rigorous quality control. We also touch on issues that may arise during communication with families. While recommendations are provided, they are not intended as proscriptive policy but rather as an addition to the general recommendations given in the International Criminal Police Organization (INTERPOL) DVI Guide, to inform preparative discussions between government officials, judiciary, police, and forensic specialists.Key points A DVI operation for an incident characterised by many fragmented and otherwise compromised human remains poses specific challenges that may prolong and complicate identifications. Specialists should be consulted at the outset to address key issues related to the aim and extent of the operation. Specialist expertise in handling compromised human remains is indispensable at the scene, in the mortuary, during reconciliation, and for quality control. Continuous consultation between representatives from government, the judiciary, law enforcement, the media, and various forensic specialists will prevent unnecessary delay and facilitate accurate and timely communication.